MICRO-COMPUTED TOMOGRAPHIC EVALUATION OF DENTINAL CRACKS CAUSED BY VARIOUS RECENT FILE SYSTEMS - Gizem Kutlu Cengiz; Hüseyin Topçuoğlu; İhsan Hubbezoğlu; Demet Altunbaş; Recai Zan (Cumhuriyet University, 2022)
Objectives: The purpose of present study was to evaluate the incidence of dentinal micro-cracks observed after the use of ProTaper Gold (PTG), WaveOne Gold (WOG), OneShape New Generation (OSNG), K3XF nickel-titanium (NiTi) instrumentation systems. Materials and Methods: Sixty extracted human mandibular first molars were randomly assigned to four groups (n = 15). The root canals were instrumented with PTG, WOG, OSNG, and K3XF systems. The cross-sectional images of the roots were screened using high-resolution micro-computed tomography imaging before and after preparation to detect the presence of dentinal cracks. Results: Although there was no statistically significant difference between PTG and WOG systems, WOG caused lesser micro-crack among all groups. K3XF showed statistically fewer cracks than OSNG. K3XF and OSNG systems caused statistically more dentinal micro-cracks than both Gold systems. WOG and PTG systems caused lesser micro-cracks formation among the systems evaluated in present study. Both Gold systems may be preferred as safer to minimize micro-cracks during root canal treatments. Conclusions: All used systems have caused different degrees of crack formations. Furthermore, WOG and PTG systems have shown superior features in terms of creating dentinal cracks according to OSNG, and K3XF systems.